1976
DOI: 10.1037/0022-006x.44.6.951
|View full text |Cite
|
Sign up to set email alerts
|

Impairment index versus T -score averaging in neuropsychological assessment.

Abstract: Neuropsychological data were obtained on 81 patients with cerebral lesions and on 87 patients presenting signs and symptoms of cerebral dysfunction but who received nonneurological discharge diagnoses. Two methods of combining neuropsychological test results were compared for percentage of accuracy in classifying subjects into appropriate groups. A standard deviation averaging method using 2'-score conversion tables for raw score data was found to be superior to the Halstead impairment index for the nonncurolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Normative data for many of the above-described tests have been provided by Kiernan and Matthews (1976). The availability of these norms permits the transformation of raw scores on individual tests into T scores (M = 50, SD = 10), thereby providing a mechanism for comparing the experimental subjects' performances against "normal expectation."…”
Section: Discussionmentioning
confidence: 99%
“…Normative data for many of the above-described tests have been provided by Kiernan and Matthews (1976). The availability of these norms permits the transformation of raw scores on individual tests into T scores (M = 50, SD = 10), thereby providing a mechanism for comparing the experimental subjects' performances against "normal expectation."…”
Section: Discussionmentioning
confidence: 99%
“…Conversion of the data to a common metric permits comparison of performance between measures, and also permits computation of summary scores (such as mean Tscores). Such T-score averaging has previously been shown to be useful (14). Although a control group was not directly examined, conversion of the data to norm-based T-scores represents an implicit comparison with control values.…”
Section: Neuropsychological Measuresmentioning
confidence: 99%
“…The accuracy rate in the interpretation of the normal elderly adult test performance was quite low and yet quite consistent with the literature on elderly persons' test performance. This literature suggests that misclassification and misinterpretation are likely to occur in the evaluation of elderly adults (Bornstein, 1986; Davies, 1968; Kiernan & Matthews, 1976; Price et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…The use of such norms can result in incorrect interpretations of test findings and lead to inappropriate recommendations for an elderly patient. For example, several studies have shown that a large percentage of normal elderly subjects are misclassified as brain damaged when standard adult norms are used (Anthony, Heaton, & Lehman, 1980; Bak & Greene, 1980; Bornstein, 1986; Cauthen, 1978; Davies, 1968; Ernst, 1987; Heaton, Grant, & Matthews, 1986; Kiernan & Matthews, 1976; Long & Klein, 1990; Mack & Carlson, 1978; Pauker, 1980; Price, Fein, & Feinberg, 1980). Reitan (1955a), in fact, demonstrated that after the age of 45, many normal persons score in the impaired range on the Halstead–Reitan Neuropsychological Battery (HRNB).…”
mentioning
confidence: 99%